Perhitungan Harga Pokok Pesanan (Job Order Costing) Produk “BRKT Number Plate K56” Pada PT. Rachmat Perdana Adhimetal - Bambang Hermanto (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2016)
The purpose of this study was to obtain information about the cost element production, the methods used and to find out the problems that occur during the decisive calculation of the cost of production of products